Perbandingan Kepuasan Pelanggan Terhadap Kualitas Layanan Logistik Pada JNE dan J&T Express di Jabodetabek - Fairuz Zalfa Shaumi; Cahyadi, Eko Ruddy (School of Business, Bogor Agricultural University (SB-IPB), 2022)
The e-commerce transactions incrase along with the increation need of logistic delivery service, causes logistic companies such as J&T and JNE compete. As a result, the goals of this study are as follows: (1) to identify the usage behavior JNE and J&T Express in Jabodetabek, (2) to analyze the level of logistic service quality attributes on perception of JNE and J&T Express user around Jabodetabek, (3) to analyze the satisfaction of both JNE and J&T Express logistic service quality, and (4) to analyze the priority of logistic quality service improvement in JNE and J&T Express. This research used descriptive analysis, IPA, CSI, radar chart, and independent sample t test. Total of 407 respondent obtained by convenience sampling. From the eighteen attributes, important services are the condition of package received safe and undamaged, company provides tracking service (web tracking), accuracy of finding the delivery destination address, the accuracy between delivery time and estimation time, guarantees for lost package. JNE has more attribute to be improved, it is in accordance with JNE’s lower CSI value compared to J&t Express causes JNE needs more effort for the improvement. Keywords: CSI, customer satisfaction, delivery service, IPA, logistic quality service